2017
DOI: 10.1097/spc.0000000000000301
|View full text |Cite
|
Sign up to set email alerts
|

Research priorities in cancer cachexia: The University of Rochester Cancer Center NCI Community Oncology Research Program Research Base Symposium on Cancer Cachexia and Sarcopenia

Abstract: Purpose Cancer cachexia remains understudied and there are no standard treatments available despite the publication of an international consensus definition and the completion of several large phase III intervention trials in the past six years. In September 2015, The University of Rochester Cancer Center NCORP Research Base led a Symposium on Cancer Cachexia and Sarcopenia with goals of reviewing the state of the science, identifying knowledge gaps and formulating research priorities in cancer cachexia throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Resistance training and aerobic training have been shown to increase muscle strength and function and represent an attractive treatment strategy for cachexia and sarcopenia [79]. No pharmacologic or nutritional intervention in the field to date has shown results superior to exercise [73].…”
Section: Interventions For Cachexia and Sarcopenia In Older Adultsmentioning
confidence: 99%
“…Resistance training and aerobic training have been shown to increase muscle strength and function and represent an attractive treatment strategy for cachexia and sarcopenia [79]. No pharmacologic or nutritional intervention in the field to date has shown results superior to exercise [73].…”
Section: Interventions For Cachexia and Sarcopenia In Older Adultsmentioning
confidence: 99%
“…In recent years, the study of exercise as a behavioral intervention in oncology and supportive care research is growing [228]. There is a tremendous need for further exploration into exercise as a therapeutic strategy for cancer cachexia [229]. In addition to its many well-described psychological and physical benefits [230], exercise interventions are easily paired with anti-neoplastic therapies and could potentially improve physical performance, a task that has proven difficult with pharmacologic anti-cachexia agents [231, 232].…”
Section: Introductionmentioning
confidence: 99%
“…A symposium conducted by the University of Rochester Cancer Center Community Oncology Program on Cancer Cachexia and Sarcopenia identified key areas for future research in area of cancer cachexia. These include: incorporating morphometrics into clinical decision making, focusing on identifying and treating patients at precachexia stages, and identifying long term biomarkers that serve as markers of changes from precachexia to cachexia, expand patient selection in cachexia trials, and identifying and incorporating realistic endpoints into clinical trials including patient reported outcomes [ 4 ]. An important development in the research into cancer cachexia was the acceptance of uniform criteria for its clinical diagnosis by Fearon et al in 2011 [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future multicenter trials examining various combinations of agents with anamorelin might pave wave for developing an effective gold standard for managing cachexia in cancer patients. Further, solely relying on BMI as an endpoint of cachexia should be limited, as owing to the growing epidemic of obesity, the proportion of patients presenting with severe weight loss and BMI < 20 continue to decline, and hence incorporating changes in muscle mass is crucial to study comprehensive effect of pharmacological agents on cachexia management [ 4 ]. Additionally, more biomarker driven clinical trials are needed in field of cancer cachexia to prospectively track changes in biomarkers associated with changes in body composition or inflammatory markers among cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation